REKONTRUKSI ECORELIGIUS ORANG MELAYU Solusi Penyelamatan Lingkungan - Husni Thamrin, M.Si (Program Pascasarjana Universitas Islam Negeri Sultan Syarif Kasim Riau, 2017)
Anthropocentric paradigm has distanced humans from nature, as well as causing the humans themselves become exploitative in attitude and do not really care about the nature. In relation, ecological crisis also can be seen as caused by mechanistic-reductionistic-dualistic of Cartesian science. The perspective of anthropocentric is corrected by biocentrism and ecocentrism ethics, particularly Deep Ecology, to re-look at the nature as an ethical community. The concept of ecoculture is already practiced from the beginning by indigenous or traditional societies in elsewhere. The perspective of the human being as an integral part of the nature, and the behaviour of full of resposibility, full of respect and care about the sustainability of all life in the universe have become perspectives and behaviours of various traditional people. The majority of local wisdom in the maintenance of the environment is still surviving in the midst of shifting currents waves by a pressure of anthropocentric perspective. There is also in a crisis because a pressure of the influences of a modernization. While others, drifting and eroding in the modernization and the anthropocentric perspective.In that context, ecoculture, particularly Deep Ecology, support for leaving the anthropocentric perspective, and when a holistic life perspective asks for leaving the anthropocentric perspective, the humans are invited to go back to thelocal wisdom, the old wisdom of the indigenous people. in other words, environmental ethics is to urge and invite the people to go back to the ethics of the indigenous people that are still relevant with the times. The essence of this perspective is back to the nature, back to his true identity as an ecological human in the ecoreligion perspective.